MUSIC ENSEMBLE LEARNING AT STATE MIDDLE SCHOOL 1 MOJOANYAR, MOJOKERTO REGENCY - -, Fajar Miftakhul Ilmi; Hidajad, Arif (Solah, 2025)
Music ensemble learning is a form of arts education activity that aims to develop musical skills, cooperation, and creativity of students. This article discusses the process and strategies of music ensemble learning at SMP Negeri 1 Mojoanyar, Mojokerto Regency. The study used a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results showed that the learning process was conducive, interactive, and able to improve students' abilities in playing musical instruments collectively. The learning strategies used included the role of the teacher as a facilitator, demonstrator, mediator, class manager, and evaluator. Music ensemble learning at this school has proven effective in increasing students' musical interests and abilities, supported by adequate infrastructure and appropriate teaching methods.